The history of Psychiatric Nursing education at the Universidade Federal de Alagoas (1976-1981) - Laila Frota Ibrahim Chamchaum; Yanna Cristina Moraes Lira Nascimento; Regina Maria dos Santos; Laís de Miranda Crispim Costa; Maria Cicera dos Santos de Albuquerque; Adnez Regina Tertuliano da Silva Cassimiro (Revista Brasileira de Enfermagem, 2021)
ABSTRACT Objective: To historically analyze psychiatric nursing teaching at the Universidade Federal de Alagoas from 1976 to 1981. Methods: Qualitative study; social-historical approach employing Thematic Oral History based on the documentary sources and testimonials from nurses, students, professors, and professionals at the psychiatric hospital where these practices occurred. The study researched World, Brazil, and Alagoas history and the Curricular Guidelines for Nursing for the history comprehension and used Erving Goffman’s concepts as a theoretical reference. Results: They revealed the structural conditions of the university in 1976, the American contribution to the teaching staff, the students’ psychological preparation in theoretical and practical classes, the precarious scenario of psychiatric care in Alagoas, and the care that minimizes stigmas through empathy and sensitive listening. Conclusion: With the emergence of that discipline, students and professors expanded their views on mental illness and emphasized their need for academic training based on reforming care principles.